2013
DOI: 10.1097/mao.0b013e31827d8aa0
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of the Completely Ossified Cochlea

Abstract: Objectives To report a novel modification of the cochlear drill-out procedure that utilizes customized microstereotactic frames as drill guides. Patient(s) A 34-year-old man with an 18-year history of profound bilateral hearing loss and completely ossified cochleae that underwent a prior unsuccessful conventional cochlear drill-out procedure in the contralateral ear. Interventions Image-guided cochlear implantation using customized microstereotactic frames to drill linear basal and apical cochlear tunnels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The extent of the surgical resection, i.e., extended round window approach, partial or subtotal cochleoectomy with or without labyrinthectomy, was based on tumor location and extension. Similar “circum-modiolar drill-out” procedures have been applied in cases of labyrinthitis ossificans ( 20 23 ). In patients with intralabyrinthine schwannomas, however, there is no ossification of the fluid spaces of the cochlea, and the tumor could be resected from the bony labyrinth after removal of parts of the cochlear capsule.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of the surgical resection, i.e., extended round window approach, partial or subtotal cochleoectomy with or without labyrinthectomy, was based on tumor location and extension. Similar “circum-modiolar drill-out” procedures have been applied in cases of labyrinthitis ossificans ( 20 23 ). In patients with intralabyrinthine schwannomas, however, there is no ossification of the fluid spaces of the cochlea, and the tumor could be resected from the bony labyrinth after removal of parts of the cochlear capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that despite progressive ossification, spiral ganglion cells can survive and result in auditory improvement following electrical stimulation. 12 Furthermore, drill-out techniques now allow cochlear implantation to be performed on progressively ossified cochleae. 8,12,13 Clinically, however, the outcomes can be negatively impacted by ossified cochleae.…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, drill-out techniques now allow cochlear implantation to be performed on progressively ossified cochleae. 8,12,13 Clinically, however, the outcomes can be negatively impacted by ossified cochleae. 8,13 We show, to our knowledge for the first time, that the cochlea can stay radiologically patent for at least six months post-operatively (75 per cent of cochleae were completely patent and 25 per cent were partially patent).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent histologic examinations of the modiolus demonstrated comparable SGN densities between injected and control groups [ 25 ]. Although our study used somewhat larger injection volumes, they did not significantly exceed the known volume of the human IAC [ 74 ]. IKVAV-PA gels have been proven safe in animal models, with no reported toxicity after injection into the nervous system or other organs [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%